CFD Modeling of a Carbonation Reactor with a K‐Based Dry Sorbent for CO2 Capture. Issue 10 (9th September 2014) - Yu, Guangbin; Dai, Bing; Chen, Juhui; Liu, Di; Yu, Xiaoyang; Shao, Junpeng; Zhao, Lei
Abstract A 2D CFD simulation of the carbonation reactor is carried out to evaluate the performance of potassium‐based dry sorbent during the CO2 capture process. A multiscale drag coefficient model is incorporated into the two‐fluid model to take the effects of clusters into account. The influence of several parameters on CO2 removal is investigated. The results indicate that increasing the reactor height and reducing the gas velocity can lengthen the residence time of particles and enhance the CO2 removal. The operating pressure has a significant influence on the performance of solid sorbents. A higher pressure will decrease the CO2 removal efficiency.